2013
DOI: 10.1093/jxb/ert030
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis HIT4 encodes a novel chromocentre-localized protein involved in the heat reactivation of transcriptionally silent loci and is essential for heat tolerance in plants

Abstract: The Arabidopsis mutant heat-intolerant 4-1 (hit4-1) was isolated from an ethyl methanesulphonate-mutagenized M2 population on the basis of its inability to withstand prolonged heat stress (4 days at 37°C). Further characterization indicated that hit4-1 was impaired specifically in terms of basal but not acquired thermotolerance. Map-based cloning revealed that the HIT4 gene encoded a plant-specific protein for which the molecular function has yet to be studied. To investigate the cellular role of HIT4 and henc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 57 publications
1
44
0
Order By: Relevance
“…To better characterize the effect of the hit5‐1 mutation on other forms of heat stress, we then compared the thermotolerance of hit5‐1 with that of hit2 and hit4‐1 mutants. These two mutants were selected because they have well‐characterized phenotypes that are defective in terms of tolerance to both prolonged heat stress (37°C for 4 d) and sudden heat shock (44°C for 30 min) treatments (Wu et al ., ; Wang et al ., ). Unexpectedly, the results showed that the hit5‐1 mutant, unlike hit2 and hit4‐1 , did not lose the capacity to endure heat shock treatment at 44°C for 30 min.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…To better characterize the effect of the hit5‐1 mutation on other forms of heat stress, we then compared the thermotolerance of hit5‐1 with that of hit2 and hit4‐1 mutants. These two mutants were selected because they have well‐characterized phenotypes that are defective in terms of tolerance to both prolonged heat stress (37°C for 4 d) and sudden heat shock (44°C for 30 min) treatments (Wu et al ., ; Wang et al ., ). Unexpectedly, the results showed that the hit5‐1 mutant, unlike hit2 and hit4‐1 , did not lose the capacity to endure heat shock treatment at 44°C for 30 min.…”
Section: Resultsmentioning
confidence: 97%
“…For example, Arabidopsis HIT1 , which encodes a membrane trafficking regulator involved in thermal adaptation of the plasma membrane, is essential for plants to tolerate prolonged heat stress (37°C for 4 d), but not heat shock (44°C for 30 min) (Wang et al ., ). In contrast, HSP101 , which encodes a molecular chaperone, is required for plants to tolerate heat shock but not prolonged heat stress (Hu et al ., ; Wang et al ., ). Therefore, a plausible scenario would be that there are at least two HSR regulators that are substrates for PFT.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…but does not reduce the induction of heat shock proteins. HIT4 associates with chromocenters and is involved in their decondensation during extended periods of heat stress [87 ]. Preceding the decondensation, HIT4 is delocalized to the nucleoli but this is not sufficient to achieve decondensation [88].…”
Section: New Non-histone Nuclear Proteins Associated With Stress Respmentioning
confidence: 99%
“…Since there is much evidence for cross-talk between signaling pathways regulating the response to abiotic stress (Jin et al 2011;Frey et al 2012;Wang et al 2013), transgenic Arabidopsis plants overexpression the ZmMAPK1 gene were generated. Three-week-old A. thaliana homozygous T 3 seedlings of the transgenic lines and WT plants were used for drought, heat and salt stress experiments.…”
Section: Overexpression Of Zmmapk1 Improves Tolerance To Drought and mentioning
confidence: 99%